Detection of landfill gas in leachate pipe and pond of a semi-aerobic landfill - Olisa, E. (Italian Association of Chemical Engineering - AIDIC, 2015)
Landfills provide very simple and affordable means of solid waste disposal, hence they are widely accepted and adopted as means for disposing off solid waste. Nonetheless, landfills pose some negative effects to the environment as a result of their production of leachate and emission of greenhouse gases. Predominant in recent landfill design and construction, aerobic or semi aerobic processes are allowed to occur within the landfill in order to hasten up the decomposition of the biodegradables in the solid waste, as well as to combat the problem of odour generation from the landfills. The semi aerobic system of landfill design is widely used in Malaysia. In this study, characterization of the various parameters which represent the organic material contained in landfill leachate, which are basically the COD and BOD5, was done. Gas sampling at the end of leachate pipes and on leachate pond surfaces were also carried out. Gas sampling bag was used to collect gas samples from the surface of leachate ponds, while a simple water displacement method was used to collect gas samples at the end of leachate pipes. Leachate samples were also collected from two different leachate ponds equalization pond and intermittently aerated pond in the semi-aerobic landfill, their COD and BOD5 values were measured and found to be in the range of 15,000-16,900 mg/L and 6,821-8,009 mg/L and 1,360-1,600 mg/L and 198-250 mg/L. The concentration of methane gas captured at the end of the leachate pipe was about 12 , while the methane gas concentration escaping to the environment from the surface of the leachate pond was about 9 . Improved form of leachate collection pipes is highly recommended for semi aerobic landfills. In-situ treatment for landfill leachate from semi aerobic landfills is highly encouraged in order to reduce the organic load of the leachate collected in leachate ponds. Copyright Â© 2015, AIDIC Servizi S.r.l.,.